Enhancing the force-velocity profile of athletes using weightlifting derivatives. - Suchomel, T. J.; Comfort, P.; Lake, J. P. (Strength and Conditioning Journal, 2017)
Weightlifting movements and their derivatives may be implemented in a sequenced progression throughout the training year to optimize the development of an athlete's strength, rate of force development, and power output. Weightlifting movements and their derivatives can be programmed effectively by considering their force-velocity characteristics and physiological underpinnings to meet the specific training goals of resistance training phases in accordance with the typical application of periodized training programs.